Peningkatan Keaktifan Berbicara Siswa Menggunakan Model Time Token - Rita Nurmala Sari (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
This research aims to improve the talking activity in Topic 2: Playing Around in My Environment of class IIC in SD Negeri Jarakan through the use of Time Token model. The data collecting methods were observation and documentation. The data analytic techniques were quantitative descriptive and qualitative descriptive. The research’s result shows that there is an improvement in class IIC’s talking activity using Time Token model. It is proven by the percentage of the students who surpassed the minimum passing criteria during learning activity which was 13,04% in pre cycle increased to 19,66% in cycle 1 and increased again to 60,86% in cycle 2. The result is supported by the observation’s result that recorded the teacher and students’ activity in using Time Token model, which was 85,29% in cycle 1 increased to 88,23% in cycle 2. The four aspects of talking activity are stating feelings, giving suggestions, asking, transferring ideas, and discussion.